2020
DOI: 10.21203/rs.3.rs-17883/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autologous bone marrow-derived mononuclear cell therapy in three patients with severe asthma​

Abstract: Background: Despite recent advances in understanding its pathophysiology and development of novel therapies, asthma remains a serious public health issue worldwide. Combination therapy with inhaled corticosteroids and long-acting β2-adrenoceptor agonists results in disease control for many patients, but those who exhibit severe asthma are often unresponsive to conventional treatment, experiencing worse quality of life, frequent exacerbations, and increasing healthcare costs. Bone marrow-derived mononuclear cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…MSC-derived EV therapy is able to upregulate IL-10 and transforming growth factor-β1 (TGF-β1), which in turn are responsible for the recruitment and expansion of regulatory T cells ( Du et al, 2018 ), decrease the number of eosinophils in both lung tissue and BALF while also modulating airway remodeling ( de Castro et al, 2017 ), and mitigate T H 2/T H 1-induced lung inflammation and airway hyperresponsiveness ( Cruz et al, 2015 ). A recent clinical study demonstrated that administration of bone marrow-derived mononuclear cells was well-tolerated and safe and improved some quality of life parameters in three patients with severe asthma ( Aguiar et al, 2020 ). Two clinical studies (NCT02192736 and NCT03137199) designed to evaluate the potential therapeutic actions of MSCs and their trophic factors in individuals with severe asthma are ongoing.…”
Section: Extracellular Vesicles In Lung Disease Pathogenesis and Thermentioning
confidence: 99%
“…MSC-derived EV therapy is able to upregulate IL-10 and transforming growth factor-β1 (TGF-β1), which in turn are responsible for the recruitment and expansion of regulatory T cells ( Du et al, 2018 ), decrease the number of eosinophils in both lung tissue and BALF while also modulating airway remodeling ( de Castro et al, 2017 ), and mitigate T H 2/T H 1-induced lung inflammation and airway hyperresponsiveness ( Cruz et al, 2015 ). A recent clinical study demonstrated that administration of bone marrow-derived mononuclear cells was well-tolerated and safe and improved some quality of life parameters in three patients with severe asthma ( Aguiar et al, 2020 ). Two clinical studies (NCT02192736 and NCT03137199) designed to evaluate the potential therapeutic actions of MSCs and their trophic factors in individuals with severe asthma are ongoing.…”
Section: Extracellular Vesicles In Lung Disease Pathogenesis and Thermentioning
confidence: 99%
“…However, there are still some issues that must be addressed before translating this therapy to humans. To the best of our knowledge, there is only one study ( Aguiar et al, 2020 ) that demonstrated the potential efficacy of MSCs in patients with asthma and one ongoing clinical trial (NCT03137199). However, these studies ( Aguiar et al, 2020 ) have limitations, such as a small sample size with no placebo-control and inflammatory biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there is only one study ( Aguiar et al, 2020 ) that demonstrated the potential efficacy of MSCs in patients with asthma and one ongoing clinical trial (NCT03137199). However, these studies ( Aguiar et al, 2020 ) have limitations, such as a small sample size with no placebo-control and inflammatory biomarkers. Procedures for cell culture need to be appropriately standardized to produce a satisfactory number of cells and should be proliferative and maintain their regeneration properties.…”
Section: Introductionmentioning
confidence: 99%